2022
DOI: 10.1038/s41467-022-30001-7
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced ynamide structural reshuffling and functionalization

Abstract: The radical chemistry of ynamides has recently drawn the attention of synthetic organic chemists to the construction of various N-heterocyclic compounds. Nevertheless, the ynamide-radical chemistry remains a long-standing challenge for chemists due to its high reactivity, undesirable byproducts, severe inherent regio- and chemoselective problems. Importantly, the ynamide C(sp)-N bond fission remains an unsolved challenge. In this paper, we observe Photoinduced radical trigger regio- and chemoselective ynamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…To elucidate the exact role of blue LED light, we measured the blue LED emission spectrum for a 40‐W Kessil blue LED lamp (Figures S4 and S5). Furthermore, we obtained the absorption spectra for the radical precursors 2 a and 2 e in 10 −2 –10 −5 M of the solvent dichloromethane (DCM) (Figures S6−S13) [12b,c] . Both 2 a and 2 e showed visible light absorption peaks for the blue LED light source, suggesting that the blue LED light initiates radical formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the exact role of blue LED light, we measured the blue LED emission spectrum for a 40‐W Kessil blue LED lamp (Figures S4 and S5). Furthermore, we obtained the absorption spectra for the radical precursors 2 a and 2 e in 10 −2 –10 −5 M of the solvent dichloromethane (DCM) (Figures S6−S13) [12b,c] . Both 2 a and 2 e showed visible light absorption peaks for the blue LED light source, suggesting that the blue LED light initiates radical formation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above control experiments, data from the literature, [3f,4f,15–16] and our previous work, [12] we suggest a plausible reaction mechanism, as shown in Scheme 6. First, 4‐methylbenzenesulfonyliodide ( 2 a ) absorbs blue LED light to produce sulfonyl ( 2 a’ ) and iodine ( 2 a” ) radicals via homolytic bond fission [12b,c] . The reactive sulfonyl radical then attacks 1 a to produce the vinyl radical intermediate A , which simultaneously produces the another vinyl radical intermediate B via 6‐ exo ‐dig cyclization with another 1 a alkyne.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20][21][22] The development of methods for synthesis of sulfones has recently attracted the attention of many researchers. [23][24][25][26][27][28] One of the most efficient methods for creating a C-SO 2 bond to obtain vinyl sulfones is the alkyne sulfonylation reaction is the addition of a sulfonyl radical to an alkyne.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to radical chemistry, ynamides behave as electron rich radical acceptors. Indeed, the relevant literature shows that, if one excepts intramolecular radical additions devised for heterocyclic synthesis, the few reported intermolecular additions to ynamides essentially involve electrophilic sulfanyl radicals . Recently, we have shown that the strategy based on atom transfer radical addition (ATRA) using ethyl α-iodoacetate, α-iodo-acetonitrile, or α-iodo- N,N -diethyl acetamide as a radical precursor is efficient in achieving this transformation.…”
Section: Introductionmentioning
confidence: 99%